Consumer adoption of Bitcoin in e-commerce - Serhatlı, Serhat. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2019., 2019)
Bitcoin has recently brought disruptive innovation into the financial system. While it is considered as an investment instrument by many, its adoption as a payment mechanism particularly in e-commerce has been scarce. Nevertheless, many e-commerce sites are considering or experimenting with it as a payment mechanism. However, the content analysis made in this thesis to identify trends and research gaps in this field shows that academic literature on the perceived benefits and risks of cryptocurrency adoption is limited. In fact, there is no prior study about cryptocurrency adoption in e-commerce payments. Accordingly, this thesis aims to explore cryptocurrency adoption in the e-commerce context to fill this gap. The cryptocurrency adoption in the e-commerce context is explored through the diffusion of innovation theory, which is expanded with perceived security, ubiquity, financial risk, and the legal risk constructs. Data is collected from 208 respondents via an online survey with convenience sampling. Frequency, crosstab, reliability, confirmatory factor analyses and partial least square estimations were conducted over the data. The results show that relative advantage, compatibility and perceived security significantly explain cryptocurrency adoption in e-commerce. In addition to that, ubiquity and trialability were significant predictors of perceived security. Finally, managerial implications are discussed for designing customer experience in cryptocurrency payments.
Keywords: Bitcoin.; Cryptocurrencies.; Electronic commerce.; Consumers -- Attitudes.